The Use of Deixis in the Traditional Pantun (Umpasa Mangampu) of Batak Toba - Achmad Yuhdi; Getsby Lewi Debora Pandiangan (Britain International for Academic Research (BIAR-Publisher), 2021)
The purpose of this study is to describe the types of deixis in the traditional pantun